Posterior cerebral artery – variation in the origin and clinical significance - Ace, Dodevski; Lazarova, Dobrila; Mitreska, Nadica; Aliji, Vjolca; Stojovska Jovanovska, Elizabeta (Macedonian Academy of Sciences and Arts, 2014)
With the introduction of new techniques in diagnostic and interventional radiology and progress in micro-neurosurgery, accurate knowledge of the brain blood vessels is essential in daily clinical work. The aim of this study was to describe the different types of PCA origin, their diameter, and to emphasize their clinical significance. In this study we examined radiographs of 53 patients who had CT angiography undertaken for a variety of clinical reasons, performed as a part of their medical treatment at the University Radiology Clinic in Skopje, R. Macedonia. This study included 24 females and 29 males, ranging in age from 32 to 73 years; mean age 55.3 ± 11.5 years. The results showed that the diameter of the posterior cerebral artery was 1.74 ± 0.317 mm on the right side and 1.98 ± 0.408 mm on the left side. The adult configuration was present in 37 (69.81%); foetal configuration was present in 12 (22.64%) and transitional configuration was present in 4 (7.54%) of the patients. We found two patients with bilateral foetal type and ten with unilateral foetal type (six on the right side and four on the left side). Despite the limitations of the study, we found that the foetal variant was presented in 22.64% of patients. Thorough knowledge of the anatomy of the intracranial vessels is important to clinicians as well as basic scientists who deal with problems related to intracranial vasculature on a daily basis.
Keywords: posterior cerebral artery; anatomy; variations; circle of Willis